Towards Collaborative and Dynamic Software Visualization in VR - Jung, Florian; Dashuber, Veronika; Philippsen, Michael (Proceedings of the 15th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications - Volume 3: IVAPP, 2020)
To improve comprehension and maintenance of distributed software systems, some software visualization tools already bundle relevant information in a graphical way, but they either focus on the static structures and dependencies, or on tracing information. Our novel visual representation lifts the software city metaphor into VR and jointly addresses both static and dynamic behavioral aspects, such as call traces of microservice based systems. Users can navigate both the traces in the time domain and the static structure in the spatial domain. They can also collaborate with other developers. We argue that our 3D visualization provides the engineer with a better grasp on relevant information. With a controlled experiment we evaluated its user acceptance.<br
Keywords: Software Visualization; Virtual Reality; Collaboration; Software Engineering; Trace Data